Rare finding of duodenal lymphangioma in a patient with Helicobacter pylori associated gastritis: A case report. Issue 47 (25th November 2022) - Waheed, Summaiya; Seetlani, Naresh Kumar; Ashfaq, Fatima; Tahir, Muhammad Junaid; Abbasher Hussien Mohamed Ahmed, Khabab; Kumari, Vineeta; Yousaf, Zohaib
Abstract : Rationale: Lymphangiomas are lymphatic malformations most commonly found in the head, neck and axilla. Their incidence in gastrointestinal tract, especially duodenum is very rare. They are mostly congenital and are usually seen in children. Owing to their asymptomatic nature, these tumors are often diagnosed incidentally. Surgical resection is the definite treatment. Patient concerns: We represent a case of a 30-year-old male with duodenal lymphangioma with presentation of intermittent dyspepsia for 1 year, partially relieved by a proton pump inhibitor. Diagnoses: Upon physical examination, there was mild tenderness observed in the epigastrium. The rest of the physical examination was unremarkable. His complete blood count report was unremarkable. Upon a negative stool for Helicobacter pylori antigen test, the patient underwent an esophagogastroduodenoscopy which revealed H pylori gastritis and a duodenal lymphangioma. Interventions: Patient was put on triple therapy (clarithromycin, amoxicillin and omeprazole) for 14 days and his symptoms improved. The lymphangioma was not resected owing to small size. Outcomes: Patient was followed till 1 year and his symptoms had improved. Lessons: The case describes a correlation between H pylori gastritis and a duodenal lymphangioma. There is likely to be an association between the two and therefore, further studies are required to find out any relationship that may exist between the 2 conditions.